Discovering the Essence of Learners: A Descriptive and Explanatory Study - Mirnawati, Mirnawati; Nani, Nurdin; Damopolii, Muljono (LP2M IAIN Palopo, 2022)
This paper intends to describe and explain the essence of students from the aspects of the definition, position, function, dimensions, and ethics. This study is significant for those who participate in the education world. This research uses a literature review approach and the researcher's reflection method. The literature method uses articles published in various recent scientific journals. In contrast, the reflection method is based on the knowledge and experience of researchers in recognising, identifying and responding to the phenomena of learners in various educational institutions. First, students are individuals experiencing a phase of development or growth in terms of physical, mental, and mind. Second, students are subjects and, at the same time, objects in education that are possible to be active, creative, and productive. Third, the dimensions of students can be understood in seven main dimensions, namely the physical dimension, the reason dimension, the religious dimension, the moral dimension, the spiritual dimension, the art dimension, and the social dimension. Fourth, the world of education has values that all parties, including students, must obey. Student ethics is a tool for students to gain knowledge and a guide in learning activities. Islam has perfectly provided basic guidelines for the ethics of learners